2007
DOI: 10.1086/520617
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and Molecular Correlates of Divergent Selection for Basal Metabolic Rate in Laboratory Mice

Abstract: Proximal mechanisms describing the evolution of high levels of basal metabolic rate (BMR) in endotherms are one of the most intriguing problems of evolutionary physiology. Because BMR mostly reflects metabolic activity of internal organs, evolutionary increase in BMR could have been realized by an increase in relative organ size and/or mass-specific cellular metabolic rate. According to the "membrane pacemaker" theory of metabolism, the latter is mediated by an increase in the average number of double bonds (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
76
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 51 publications
9
76
1
1
Order By: Relevance
“…Our results illustrate a recurring conundrum in similar studies, such as in experimental evolution studies [28] or studies controlling for body mass and phylogeny [26] that seldom find strong support for the pacemaker hypothesis. Nonetheless, we did find a direct relationship between FlightMR and the abundance of the saturated FA 16 : 0, after controlling for body mass and phylogeny (figure 5).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Our results illustrate a recurring conundrum in similar studies, such as in experimental evolution studies [28] or studies controlling for body mass and phylogeny [26] that seldom find strong support for the pacemaker hypothesis. Nonetheless, we did find a direct relationship between FlightMR and the abundance of the saturated FA 16 : 0, after controlling for body mass and phylogeny (figure 5).…”
Section: Discussionsupporting
confidence: 60%
“…Here, insects were used to examine the relationship between membrane composition and metabolic rate, and we report evidence of such a pattern outside the chordates. The resulting implications for the pacemaker hypothesis could be important if strong support can be demonstrated across phyla, because recent research questions its validity [26,[28][29][30]. Furthermore, we test the pacemaker hypothesis using an intermediate phylogenetic scale (within the orchid bee tribe, Euglossini).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Metabolic intensity of tissues may vary because of differences in mitochondria (Else and Hulbert, 1985;Moyes, 2003;Porter, 2001;Suarez, 1996), concentrations of metabolic enzymes (Garrido et al, 1996;Marsh and Dawson, 1982;Vézina and Williams, 2005;Weber and Piersma, 1996), activity of the membrane sodium pump (Wu et al, 2001) and fatty acid composition of cell membranes (Brzek et al, 2007;Hulbert and Else, 2005). Variation in BMR between lowland tropical birds and their temperate counterparts could arise if the relative size of some or all of the central organs in tropical species were smaller .…”
Section: Introductionmentioning
confidence: 99%
“…An inherent, positive coupling between DEE and BMR may occur either centrally, because an increase in the size of energetically expensive digestive organs is required to process more Individual (co)variation in metabolism food (Brzęk et al, 2007;Daan et al, 1990;Konarzewski and Diamond, 1995;Selman et al, 2001), or peripherally, if the tissues at the site of energy use reach maximal capacity, which may also require high maintenance costs such as mammary glands (Hammond et al, 1994). However, recent theoretical and empirical work has suggested that DEE should not be limited to a fixed ratio of BMR.…”
Section: Introductionmentioning
confidence: 99%